ChemInform Abstract: RE3Au5Zn (RE: Y, Sm, Gd—Ho) — A New Structure Type with Five‐ and Six‐Membered Rings as Building Units in a Gold Network. Issue 32 (22nd July 2016) - Gerke, Birgit; Poettgen, Rainer
Abstract: Polycrystalline Ln3 Au5 Zn (Ln: Y, Sm, Gd—Ho) intermetallics are prepared by melting of stoichiometric mixtures of elements (sealed Ta tubes in evacuated quartz tubes, 1.